2017
DOI: 10.12669/pjms.336.13628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal morphological characteristics between diabetic and non diabetic population

Abstract: Objective:To compare corneal morphological parameters between diabetics and age matched non-diabetic control subjects and to evaluate the correlation of these parameters in relation to duration of diabetes mellitus (DM), glycemic status and severity of diabetic retinopathy.(DR).Methods:This cross sectional comparative study was conducted at the Department of Ophthalmology, PNS Shifa Karachi from February 2016 to January 2017. Patients with ages between 10 to 80 years of either gender who were diagnosed to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
3
21
1
Order By: Relevance
“…Our findings regarding ECD de- crease were in accordance with the majority of previous studies. Specifically, Inoue et al [11] found a 4.1% reduction in ECD in patients with DM compared to controls in line with other authors, who also reported a significant reduction in ECD in diabetic patients [9,10,[14][15][16][17][18][19][20]. However, there is no absolute consensus in the literature.…”
Section: Discussionmentioning
confidence: 76%
“…Our findings regarding ECD de- crease were in accordance with the majority of previous studies. Specifically, Inoue et al [11] found a 4.1% reduction in ECD in patients with DM compared to controls in line with other authors, who also reported a significant reduction in ECD in diabetic patients [9,10,[14][15][16][17][18][19][20]. However, there is no absolute consensus in the literature.…”
Section: Discussionmentioning
confidence: 76%
“…Calvo-Maroto et al [139] studied the effect of diabetes duration and poor glycemic control on the endothelial cell population: they found that the longer the evolution time of diabetes, the greater the loss of endothelial cells; this could be the reason why we find more differences in T1D patients, who are generally of a younger age at disease onset and usually present a longer duration of diabetes evolution. Islam et al [138], Anbar et al [136], and Urban et al [133] also found this correlation between diabetes duration and ECD.…”
Section: Diabetes and Endotheliummentioning
confidence: 79%
“…Regarding endothelial characteristics, diabetes patients seem to have higher rates of polymegathism and lower percentages of hexagonality (higher polymorphism) [79, 131, 136, 137]. Moreover, Anbar et al [136] and Islam et al [138] found a significant correlation between the duration of diabetes and pleomorphism and polymegathism, supporting the idea that the longer the disease evolution, the more the endothelial alteration.…”
Section: Diabetes and Endotheliummentioning
confidence: 97%
“…In a population-based cross-sectional study, Sudhir et al [20] reported that ECD was significantly lower in diabetic patients than in controls, but there was no significant difference between groups regarding hexagonality % or CV of cell size. Islam QU et al [21] reported that the mean ECD was significantly lower in diabetic patients than in agematched healthy controls, but the mean average cell size, CV and hexagonality were not significantly different between the two groups. Similar to our results, the duration of diabetes was significantly correlated with ECD and hexagonality.…”
Section: Discussionmentioning
confidence: 96%